In-vitro screening of antifungal activity of plants in Malaysia - Nazmul, M.H.M.; Salmah, I.; Syahid, A.; Mahmood, A.A. (Biomedical Research Press, 2011)
Twelve species of local Malaysian plants and 5 strains of medically important fungi were se-lected for this study. Antifungal susceptibility test was performed to screen the antifungal activity of these plants against the selected fungi. Piper betel produced the best result in anti-fungal susceptibility testing and showed to possess antifungal property against 4 out of 5 strains of the fungus. Solid Phase extraction (SPE) technique was applied to Piper betel to achieve initial separation of active antifungal compound in the form of methanol fractions. These fractions were tested for their antifungal property. Piper betel showed the best anti-fungal activity especially against Trichophyton rubrum.